Comprehensive studies on the electrical transport of some chalcogenide semiconductors: frequency- and temperature-dependent AC conductivity - Ojha, Swarupa; Chamuah, Anil; Roy, Madhab; Bhattacharya, Sanjib (Frontiers in Physics, 2023)
AC conductivity of chalcogenide semiconductor doped with Ag2S has been extensively studied not only for applications in devices but also for interests in academics. X-ray diffraction study reveals the presence of GeS, Ag2S, Se5.1S1.9, Se2.57S5.43, Ag2Se, S3Se5, Se4.7S3.3 and Ag8S nanocrystallites. The characteristics vibration appeared in the range 500-600cm-1 is due to the Ag-S bond and the vibrations at 3700 and 1600cm−1 can be assigned as the bending and stretching vibrations of O-H bond which may be formed due to the adsorption of H2O molecules on Ag2S surface. DC electrical conductivity can be increased by optical phonon frequency which may be involved in the enhancement of structural vibrations.At low temperature, “Density of States” increases from 3.337 x 10 19 to 2.396 x 10 21 eV– 1 cm – 3 and at high temperature, it enhances from 3.417 x 10 28 to 1.1356 x 10 31 eV– 1 cm – 3. Correlated Barrier Hopping model explores the maximum barrier height for composition, x = 0.1 as 0.0292 eV. Modified Non-overlapping Small Polaron Tunneling model reveals the polaron transfer activation energy for x = 0.2 as 0.09110 eV. The independency of electrical relaxation process of the system on temperature and its dependency on composition was exhibited by the scaling of the conductivity spectra.